2010
DOI: 10.1080/1350293x.2010.525931
|View full text |Cite
|
Sign up to set email alerts
|

The outdoor environment in Norwegian kindergartens as pedagogical space for toddlers' play, learning and development

Abstract: En studie kring pedagogers syn på utomhusvistelse i förskolan SammanfattningDenna studie handlar om vad pedagoger har för syfte med utevistelsen. Hur pedagogerna ser på utemiljön och på vilket sätt den kan tas tillvara. Förskolan ska göra barnen uppmärksamma på miljön runtomkring (Skolverket, 2010). Studien tar upp vilka faktorer pedagogerna anser vara värdefulla för barns utevistelse. Studien belyser också hur pedagogerna värderar sin roll ute och till sist hur pedagogerna arbetar med det styrdokument försko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 5 publications
4
64
0
11
Order By: Relevance
“…The physical performance of preschool children and the outdoor environment as pedagogical space for toddlers have been described previously (Krombholz 2006(Krombholz , 2012Moser and Martinsen 2010). Furthermore, previous studies in childcare settings have mostly quantified children's PA or described the association between PA and the facilities available at the centres (e.g.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…The physical performance of preschool children and the outdoor environment as pedagogical space for toddlers have been described previously (Krombholz 2006(Krombholz , 2012Moser and Martinsen 2010). Furthermore, previous studies in childcare settings have mostly quantified children's PA or described the association between PA and the facilities available at the centres (e.g.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…This knowledge could also be useful for ECEC politicians and practitioners in other countries since Norwegian ECECs spend a large proportion of their time outdoors (Helsedirektoratet 2012;Moser & Martinsen, 2010), and the Norwegian ECECs give children a high degree of free mobility and play, including the possibility for risky play types (Little, Sandseter, & Wyver, 2012;Sandseter, 2010Sandseter, , 2012. It seems that even though Norwegian children are, to a high degree, exposed to situations that can lead to injuries, the rate of injuries is very low.…”
Section: Resultsmentioning
confidence: 99%
“…Since Norwegian children spend a large proportion of their time in ECECs in play and outdoor activities (Helsedirektoratet 2012;Moser & Martinsen, 2010), it is not a surprise that most injuries occur outdoors. A somewhat older English study (Illingworth et al, 1975) showed that even though most injuries in playgrounds were scrapes, bruises and small cuts, the amount of fractures was quite substantial (26.5 %) while concussions were considerably lower in occurrence (6 %).…”
Section: Characteristics Of Injuries In Norwegian Ececsmentioning
confidence: 99%
“…Physical environment is here understood to be the building, the architectural design of the space, interiors and furnishings as well as the toys and materials in this space. An examination of the external physical play area based on the same data, has already been described in a previous article, which is why it is not considered in this context (Moser & Martinsen, 2010). Buildings and their design express ideology, financial constraints and the interests of the child and childhood.…”
Section: Structural Conditions For Play In Kindergartensmentioning
confidence: 99%